(untitled) (Filološke studije, 2019)
The paper investigates variability of nature images among senior children, Tartar village dwellers and Russian urban dwellers, living in one and the same region in Russia. On the basis of comparative analysis of associative-verbal networks, constructed on the bilingual material, the degree of closeness of associative fields of Russians and Tartars is revealed; the functions of universal, variable and specific semantic links in organizing images of the surrounding world and in cross-cultural communication between different social groups (village and urban dwellers) and ethnos (Tartars and Russians) are determined.